Quality of life impairment in patients of obstructive sleep apnea and its relation with the severity of disease - Dutt, Naveen (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Several studies have demonstrated considerable impairment of quality of life (QOL) in obstructive sleep apnea (OSA) patients, but its relation with severity of OSA is yet unclear. STUDY OBJECTIVES: To investigate the effects of OSA on the QOL and its association with the disease severity. DESIGN AND SETTING: Observational, prospective case-control study. MATERIALS AND METHODS: QOL of 69 OSA patients and 41 healthy controls were assessed using the Calgary sleep apnea quality of life index (SAQLI) on the morning following the polysomnography (PSG) study. STATISTICS: All statistical analyses were performed using the SPSS 17.0 (SPSS Inc., Chicago). Differences between sleep-related symptoms and SAQLI subscales scores were assessed with the Chi-square test and the Student t-test. Due to non-normal distribution, differences between SAQLI scores of controls and OSA patients were evaluated using a non-parametric Mann-Whitney test. Spearman correlation and backward multiple regression analysis were used to analyze the association between SAQLI scores and sleep indices and anthropometric variables and PSG variables. RESULTS: Study included 69 cases (57 male and 12 females) with a mean age, weight, height, neck circumference, and body mass index 48.45 ± 10.12 years, 83.03 ± 16.48 kg, 159.75 ± 28.29 cm, 44.01 ± 3.23 cm and 30.77 ± 6.71 kg/m(2). Mean apnea-hypopnea index was 26.39 ± 16.62. The median score of four SAQLI domains daily function, social interaction, emotional, symptoms and total mean SAQLI score were 3.64 (3.46-3.90), 3.77 (3.51-3.88), 3.64 (3.53-3.83), 4.80 (4.68-5.11), 4.09 (3.88-4.09),and 1.36 (1.29-1.71), 1.38 (1.24-1.62), 1.45 (1.23-1.62), 2.00 (1.78-2.26), 1.55 (1.46-1.73) for patients and controls respectively. All the individual domain scores and the mean SAQLI scores of patients were significantly higher than the controls. CONCLUSION: OSA causes significant impairment of QOL, but the severity of impairment is not directly proportional to the severity of OSA.